Democracy Education in Primary Social Science: Findings of a Design-Based Research Study on the Promotion of Democratic Conflict Skills (Pedagogical Horizons, 2025)
Education for democracy is considered effective if it is given to all young citizens “from the very beginning”, from primary school onwards. In times of increasing political polarization, the promotion of democratic conflict skills appears to be a particularly important educational goal. The project presented (LPSU) aims to make a contribution to this. It aims to develop and evaluate a lesson plan for elementary school science lessons. Initial results of a design-based research study conducted for this purpose show, on the basis of qualitative interviews and lesson observations, that primary school children have different levels of prior political knowledge, are very willing to make political judgments and gain certain democratic insights from the lessons they experience.